Conductors for change: a framework of conductor competencies for supporting adolescent male choral singers - Murphy, Brian (Royal Irish Academy of Music, 2026)
The issue of the ‘missing male’ in non-liturgical choral music programmes is well established, with adolescent boys disproportionately leaving choirs during puberty. This loss has long-term consequences for choirs, particularly in recruiting tenors and basses. At the heart of this issue is adolescence, a complex period of physical, psychological and social development during which boys navigate new voices and musical identities, experience vulnerability and uncertainty and risk disengagement. This study focuses on conductors and their impact on boys’ choral experiences during this transitional stage, examining the knowledge, skills and behaviours required to sustain participation, support vocal health and foster positive musical experiences. There is a clear gap in conductor education, as conductors are rarely prepared systematically to support adolescent males through voice change and to respond to the other ways puberty impacts on their choral participation. This research addresses that gap through a combination of literature analysis, a survey of training provision and semi-structured interviews with ten conductors working in Ireland and Northern Ireland. This research brings together models and frameworks describing conductor competencies, revealing limited guidance specific to the cambiata stage, together with research specific to the participation of adolescent males in choral contexts. The survey of training provision confirms that existing professional development largely focuses on general skills and knowledge, offering little preparation for the specialised challenges of working with changing voices. Interviews with practitioners offer practical insights into effective behaviours, strategies and reflective practices, showing how conductors respond to these challenges in real-world settings. Based on this evidence, the study develops the first comprehensive, research- and practice-informed framework of competencies for conductors working with adolescent males during voice change. The framework outlines competencies across musical, pedagogical and interpersonal domains. Mentorship is highlighted as a particularly important competency, offering both a model for developing conductor capability and a means of supporting boys effectively. In addition to deep musical and pedagogical competence, the framework emphasises the role of the conductor in nurturing social, emotional and identity development through reflective, evidence-informed practice. By combining practitioner experience with research, the framework bridges theory and practice, providing a concrete resource for professional development, curriculum design and reflective practice. It also establishes a foundation for future research, including its evaluation and iteration for use in different contexts and the direct inclusion of boys’ perspectives to ensure responsiveness to their needs and motivations. This study makes an original contribution by integrating conductor competency models with scholarship on adolescent male voice change, providing a structured pathway to enhance professional practice, sustain boys’ engagement in choral singing and support the long-term success of the choral field.
Keywords: HUMANITIES and RELIGION::Aesthetic subjects::Music; Choirs; Male voices; Singers; Singing; Boys; Choral conducting - Instruction and study; Choral singing - Instruction and study; Adolescents